Medical negligence: judicial process affecting Bolam principle / Ku Abdul Rahman Ku Ismail - Ku Ismail, Ku Abdul Rahman (2010)
This dissertation is about the judicial process by various jurisdictions affecting Bolam principle, the traditional pillars of medical law which responds to the growing interest in medical negligence, a common form of medical malpractice. It is about medical practitioner's standard of care and the patient's autonomy. Medical practitioners are increasingly confronted by ethical issues involving the issues arising from the provisions of information, diagnosis and treatment in relation to duty and standard of care expected from the medical practitioners in administering patients while in their care. The first part of the Bolam principle mentions that the doctor is not negligent if he has acted according to an accepted medical practice. A practice accepted as proper by a responsible body of medical opinion. If the doctor has complied with this practice, there is strong evidence that the doctor is not negligent, regardless of whether there is more than one accepted practice by other bodies of responsible medical opinion. Medical ethics stress the autonomy of the patient or recipient of health care. Often known as self-determination which sees human beings as having unconditional intrinsic value and having the capacity for rational choice where in order to be autonomous, a person must be free of external control as well as be in control of his affairs with exception of some persons who cannot act autonomously because they are incapacitated, ignorant, immature or coerced. From time in memorial, medical practices had been regarded as a noble profession in United Kingdom and other jurisdictions. Since then, it is evidenced that the courts had demonstrated its judicial attitude in protecting this noble profession and indirectly discouraging medical claims or litigations against the doctors in the event of negligence or mishaps. The issue of doctors' negligence in treating their patients became a great concern of the public. The common law developed and it is accepted that doctors owe a duty of care to their patients. The controversial issues in this area of law is particularly on the standard of care expected from the doctors in treating their patients while in their care is unavoidable. The judges in court of laws then developed principles and approaches in confronting or resolving this thorny issue. In 1957 McNair J in Bolam v Friern Hospital Management Committee (1957) 1 WLR 582 profounded a test commonly known as the Bolam test to resolve the issue of standard of care expected from a doctor. This test seems to strengthen the shield that protected the medical practitioners against medical litigation whereby total reliance on the opinion of the medical experts is the deciding factor on this issue.